RANCANG BANGUN SISTEM INFORMASI PERMINTAAN ATK BERBASIS INTRANET (STUDI KASUS: KEJAKSAAN NEGERI RANGKASBITUNG) - Eka Wida Fridayanthie; Tias Mahdiati (Universitas Bina Sarana Informatika, 2016)
The development of information technology is growing rapidly in all areas of influence, while the computer is a device created to facilitate human work in supporting these developments. The technological developments which led to the need for information quickly, precisely and accurately becomes very important. With the computerized system, expented all the work can be easily done with good result. The purpose of making this website other than to make the scripsi, as well as to help solve the problems that occur at Kejaksaan Negeri Rangkasbitung. The case with at Kejaksaan Negeri Rangkasbitung is the absence of a website to be able to facilitate the parties concerned to find out information relating to the job. So far information on the Kejaksaan Negeri Rangkasbitung can not be fully utilized by the parties concerned due to lack of knowladge and human resources who are competent in the field of information technology. The author provides a discussion restriction only on the demand for office stationery.Keyword: Business Applications, Sales Activities, Information Systems